Regional Convergence and Spatial Shift-Share Analysis of Labor Productivity in Indonesia - Wahyuni, Ribut Nurul Tri (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This study offers a new method to analyze district labor productivity in Indonesia.Research Objectives: This study examines the convergence of district labor productivity in Indonesia and the role of structural change in this district labor productivity growth.Research Methods: This study uses spatial convergence and spatial shift-share analysis. This study collected data from BPS-Statistics Indonesia at the district level between 2010 and 2022.Empirical Results: Labor productivity in Indonesia exhibits convergence. Neighbor districts' characteristics, such as initial labor productivity and unobserved variables, affect this convergence. The intrasectoral component has the most significant effect on labor productivity growth. The intersectoral component, caused by structural change, has almost no effect.Implications: The Indonesian government can improve intrasectoral productivity growth to accelerate labor productivity development.JEL Classification: C21, E24, R11